2008
DOI: 10.1111/j.1440-1673.2008.02003.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of percutaneous endoscopic gastrostomy versus nasogastric tubes for enteral feeding in head and neck cancer patients treated with (chemo)radiation

Abstract: Percutaneous endoscopic gastrostomy (PEG) tubes have largely replaced nasogastric tubes (NGT) for nutritional support of patients with head and neck cancer undergoing curative (chemo)radiotherapy without any good scientific basis. A randomized trial was conducted to compare PEG tubes and NGT in terms of nutritional outcomes, complications, patient satisfaction and cost. The study was closed early because of poor accrual, predominantly due to patients' reluctance to be randomized. There were 33 patients eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
128
2
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(150 citation statements)
references
References 14 publications
10
128
2
10
Order By: Relevance
“…A total of 11 RCTs were included in the systematic review ( Table 2) (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Four trials explicitly stated they included patients with CVA complicated by dysphagia (36,38,41,42).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 RCTs were included in the systematic review ( Table 2) (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Four trials explicitly stated they included patients with CVA complicated by dysphagia (36,38,41,42).…”
Section: Resultsmentioning
confidence: 99%
“…Although a randomized study that closed early because of poor accrual showed PPEG is not different from a nasogastric tube in maintaining weight during radiation treatment (Corry et al, 2008). Then PPEG is occasionally a needless procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Zum Vergleich zwischen nasogastralen und perkutanen Sonden liegen eine RCT [295], 2 retrospektive Vergleiche [292,296] sowie 2 Cochrane-Analysen [272,297] und 2 weitere systematische Reviews vor [298,299]. Diese Publikationen berichten für beide Methoden über vergleichbare Wirksamkeit auf das Körperge-wicht [295,296] und vergleichbar geringe Komplikationsraten [295,297,298] sowie keine Unterschiede im Überleben [299]; allerdings verrutschen nasogastrale Sonden sehr viel leichter (relatives Risiko PEG/NG = 0,17) [299] und es kommt häufiger zum Interventionsversagen (PEG 12 % vs. NG 40 %) [297]. Auffällig ist dagegen, dass eine PEG-Ernährung deutlich länger durchgeführt wurde als eine nasogastrale Ernährung (Liegedauer 28 vs. 8 [292] bzw.…”
Section: Leitlinie E10unclassified